Direitos humanos e o inimigo hoje consolidação das instituições democráticas no âmbito da Justiça Criminal no Brasil - Souza, Vanessa Cristina de (2014)
In order to understand the formation of the justice system and its relationship to democracy as a fundamental condition for the realization of human rights, this work aims to deepen the debate on Criminal Justice through the analysis of existing formal and informal mechanisms of social control institutes of law, from the study of historical changes related to the formation and consolidation of democratic institutions, to analyze the criminal law of postmodernity and excessive use of authoritarian repressive instruments of law in democratic States as a way to curb crime that considered an enemy of society, with the construction of the debate on the punitive power of the State and its current monopoly of violence, addressing the extent to which this is legitimized and justified in Democratic States Law